Comparison the New Kinetics Equation of Non-competitive Sorption Cd(II) and Zn(II) onto Green Sorbent Horse Dung Humic Acid (HD-HA) - Rahmat Basuki; Ngatijo Ngatijo; Sri Juari Santosa; Bambang Rusdiarso (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
The new kinetics equation has been proposed and applied to the sorption of Cd(II) and Zn(II) onto green sorbent horse dung humic acid (HD-HA). This work aims to study the new kinetics equation and to compare its parameters with Lagergren and Ho kinetics equation in the same system. HD-HA was extracted and purified by Stevenson’s methods and then characterized by detection of its functional group, UV-Vis spectra, and total acidity. The sorption study of this work was investigated by batch experiment in pH optimum 5. Langmuir’s monolayer sorption capacity (b) of Cd(II) and Zn(II) onto HD-HA was 1.329×10-3 and 1.070×10-3 mole.g-1, respectively. Langmuir equilibrium constant (KL) of Cd(II) and Zn(II) sorption was 5,651 and 6,399 (mole/L)-1, respectively. The kinetics parameters were determined by Lagergren, Ho, and the new kinetics equation. The best linearity (R2) and the most fitted sorbed metal ion in equilibrium (xe) with the experimental data was the Ho kinetics equation. However, the correct value of sorption rate constant (ka) was not really known, because the ka resulted from Ho and Lagergren kinetics equation can not be compared with another parameter and there is no scale to measure the correctness of this value of ka. In this work, the correctness value of ka of the new kinetics equation can be measured by ka/kd equal to K, and this K should be equal to KL. The values of K of Cd(II) (3,452 (mole/L)-1) and and Zn(II) (10,898 (mole/L)-1) were quite similar with KL. Additionally, the value of intercept from linear regression of this new kinetics equation (Cd(II) = 6.8517; Zn(II) = 6.0408) was highly similar with the manually calculation of -ln(xe/ab) (Cd(II) = 7.0638; Zn(II) = 6.9838). These new kinetics equations also reveal that Lagergren sorption rate constant (kLag) is the complex function of ka(ab-xe2)/xe).